Hubungan Stresor Lingkungan dengan Kenyamanan Pasien - Manurung, Idawati; Khasanah, Lailatul; Kodri, Kodri (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT The environment in a patient's hospital room can play a significant role in their mental state and recovery process. Factors such as hygiene, room temperature, and noise levels can increase a patient's stress and discomfort levels. This study aims to determine the relationship between environmental stressors and patient comfort, The study was conducted at Dr. A. Dadi Tjokrodipo Hospital in Bandar Lampung in May 2023. The study used quantitative and Chi-Square methods and involved a questionnaire to measure environmental stressors and patient comfort. The population was patients in the surgical ward, with a sample of 90 respondents. The results indicated that most patients felt that environmental stressors (including hygiene, room temperature, and noise) were highly disruptive, and they felt very uncomfortable due to these factors. There was a statistically significant relationship between environmental stressors and patient comfort. In conclusion, environmental stressors such as hygiene, room temperature, and noise can significantly disrupt a patient's comfort during their treatment. Patient comfort can be improved by controlling these factors, and the room temperature was found to have the most significant impact on patient comfort. Hospitals must prioritize cleanliness, coolness, and tranquility of the inpatient environment to minimize patients' stress levels. Keywords: Stressors, Environment, Comfort, Patient.  ABSTRAK Lingkungan fisik ruang rawat inap mempengaruhi psikologis dan proses kesembuhan pasien. Ruang rawat yang tidak bersih, gerah dan bising akan meningkatkan stres dan ketidaknyamanan pada pasien. Tujuan penelitian untuk mengetahui hubungan stresor lingkungan dengan kenyamanan pasien. Jenis penelitian ini kuantitatif, dengan metoda Kai Kwadrat di Rumah Sakit Dr. A. Dadi Tjokrodipo, Bandar Lampung, Mei 2023. Populasi penelitian pasien rawat inap bedah dengan sampel 90 responden. Hasil penelitian menunjukkan bahwa pada lebih banyak pasien yang merasa terganggu dengan stresor lingkungan (kebersihan, kegerahan dan kebisingan) dan lebih banyak pasien yang merasa tidak nyaman.  Hasil analisis menunjukkan ada hubungan bermakna antara stresor lingkungan dengan kenyamanan pasien. Kesimpulan, stresor lingkungan seperti kebersihan, kegerahan dan kebisingan sangat mengganggu kenyamanan pasien selama di rawat. Kenyamanan akan meningkat bila variabel kegerahan, kebersihan dan kebisingan dapat dikontrol dan yang paling besar pengaruhnya terhadap kenyamanan pasien adalah kegerahan atau kesejukan ruangan. Saran, rumah sakit harus tetap memperhatikan kebersihan, kesejukan dan ketenangan lingkungan rawat inap karena itu akan mengurangi stres pasien.  Kata Kunci: Stresor, Lingkungan, Kenyamanan, Pasien